Penelitian Korelasional Dan Kausalitas: Pengertian, Proses Dasar, Ragam, Dan Desain Penelitian Korelasional, Analisis Dan Interpretasi Data - Basri saenong; Umar suleman; Ulfiani rahman (Advances In Education Journal, 2025)
Correlational and causal research are two fundamental approaches widely used in social and educational research to understand relationships among variables. Correlational research focuses on identifying the strength and direction of relationships between two or more variables without manipulating them, whereas causal research aims to determine whether changes in one variable directly cause changes in another. This paper discusses the definition, basic processes, types, and designs of correlational research, as well as data analysis and interpretation in relation to causality. Using a literature-based approach, the study examines key concepts of correlational research, including simple, partial, and multiple correlations, along with common research designs such as cross-sectional, longitudinal, and predictive studies. The discussion highlights the importance of appropriate statistical techniques, careful interpretation of results, and awareness of confounding variables. The findings emphasize that correlation does not necessarily imply causation and that stronger research designs are required to establish causal relationships. This study provides a conceptual foundation for researchers in designing valid, reliable, and methodologically sound studies in social and educational contexts.